15 Transcutaneous electrical acupoint stimulation (TEAS) improves IVF outcome in patients receiving vitrified-warmed embryo-transfer. (March 2019) - Zhong, XF; Jiang, XM; Yin, P; Yan, H; Heng, BC; Zhang, WW; Tong, GQ
Abstract : Background: To investigate the effects of TEAS on the clinical outcome of IVF patients receiving vitrified-warmed embryo transfer. Methods: 120 patients were randomly allocated into the TEAS treatment group and untreated control group. Endometrial thickness, morphology, blood flow, endometrial receptivity related gene expression and clinical pregnancy rates were compared between the two groups. Results: In the TEAS group, endometrial blood resistance significantly decreased after TEAS was administered, with the blood resistance index and systolic peak value and the end-diastolic velocity of blood flow being significantly lower (p<0.05) than that of the control group. Endometrial thickness and percentages of type A and type AB endometrium were higher in the TEAS group (p>0.05). Expression levels of endometrial receptivity related genes, such as ITG beta 3, IL1, IL5, IL8, CCL3, CCL4, CCL8, HOXA10, were higher in the TEAS treatment group than in the control group. TEAS treatment resulted in an increased clinical pregnancy rate, although this was not statistically significant (55.56% vs 40%) (p>0.05). Conclusion: TEAS treatment significantly decreases blood flow resistance in the endometrium and increases expression levels of endometrial receptivity related genes. TEAS tends to increase endometrium thickness and improve endometrial morphology, which resulted in an increased clinical pregnancy rate.